The initial and continuing training of Physical Education teachers for application of competency model: a qualitative study - Zapatero Ayuso, Jorge Agustín; Campos Izquierdo, Antonio; González Rivera, María Dolores (Revista Complutense de Educación, 2017)
This study seeks to understand how a group of Physical Education teachers acquired their training to teach competence, and the valuation of its modes of acquisition. The sample was constituted of six secondary school teachers, men and women, from beginners to expert, who exercised teaching in high schools in the north, south, east and center of the Community of Madrid. Techniques as semistructured interviews and focus group were triangulated. The information collected was analyzed following proper procedures inductive model of “Grounded Theory”. The results indicate that the initial training is postulated as the type of training that most favors the application of teaching competencies, especially among beginners teachers. Also, experts participants consider their initial training is an advantage to develop the model. However, participants report making few training activities on the competency model in Physical Education and not appear to be directed toward principles. These results suggest the possibility of developing the training (initial or continuing) teacher on the competency model as a means for applying a model that promotes social inclusion, employability and active citizenship of students.